Simple method for purification of acrylamide and N,N'-methylene-bisacrylamide solutions - Michov, B.M.
Analytically pure solutions of acrylamide and N,N'-methylene-bisacrylamide (bis)are necessary for preparing qualitative polyacrylamide gel. These solutions very often contain acrylic acid, ammonia, other substances, and chains of spontaneously polymerized acrylamide. The admixtures make the solutions yellowish and catalyze the polymerization process.
Keywords: ACRYLAMIDE; ACTIVATED CARBON; N,N' METHYLENEBISACRYLAMIDE; CRYSTALLIZATION; FILTRATION; INTERMETHOD COMPARISON; LETTER; POWDER; PURIFICATION; ROOM TEMPERATURE